2018
DOI: 10.3846/tede.2018.6056
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Technological Innovation in Smes: A Bayesian Network Analysis of Eu Regional Policy Impact on Polish Firms

Abstract: We study the underlying mechanisms of technological innovation in SMEs in the context of ex-post evaluation of European Union’s regional policy. Our aim is to explain the observed change in firms’ innovativeness after receiving EU support for technological investment. To do so, we take an approach that is novel in innovation studies: a Bayesian Network Analysis to assess the effectiveness of EU policy instrument for technological innovation and to determine the mechanisms by which the policy works within firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…However, this strategy might cause corruption, and thus lead to the under-efficiency of subsidies [ 4 , 6 ]. For example, it is argued that governments contribute more to corporations with better financing in Poland [ 21 ]. Thus, many studies indicate distortion of resource allocation by public bureaucracies [ 9 ], and argue that the political resource curse effect and crowding out effect may hinder corporate innovation and its performance [ 6 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…However, this strategy might cause corruption, and thus lead to the under-efficiency of subsidies [ 4 , 6 ]. For example, it is argued that governments contribute more to corporations with better financing in Poland [ 21 ]. Thus, many studies indicate distortion of resource allocation by public bureaucracies [ 9 ], and argue that the political resource curse effect and crowding out effect may hinder corporate innovation and its performance [ 6 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…A similar study of innovation utilising Bayesian networks is cited by Kim and Park (2008) and Florio et al (2018). Kim and Park (2008) applied the Bayesian network as a methodology to investigate the impact of R&D collaboration on innovation performance among Korean companies.…”
Section: Bayesian Network Analysis: New Methodology In Innovation Res...mentioning
confidence: 99%
“…In this study, a causal chain was presented between variables and R&D collaboration had a significant impact on process innovation, but it did not affect product innovation, and government support was the most important factor for product innovation. Florio et al (2018) studied the mechanisms of technological innovation for small and medium-sized Polish enterprises in terms of evaluating the EU's regional policies. Explaining the change in innovation of companies after being supported by technology investment through Bayesian networks, they claimed that Bayesian network analysis confirmed that Technological Credit is taking a link between the adoption of new technologies and the discovery of new overseas markets.…”
Section: Bayesian Network Analysis: New Methodology In Innovation Res...mentioning
confidence: 99%
“…Survey responses were complemented with data on the volume of ERDF support provided, the types of projects funded and additional variables made available by the Managing Authorities on the beneficiary firms (such as their sector and size). 7 More information on the instruments, their theory of change, the sample of respondent firms, and details on all the analyses performed can be found in the European Commission report (2015) and in the related working papers by Sirtori et al (2017) and Florio et al (2017). Here our aim is not to discuss in detail the theory of each policy intervention and the results of our evaluation.…”
Section: Bna Applied To the Evaluation Of Business Supportmentioning
confidence: 99%